2021
DOI: 10.3389/fnut.2021.708271
|View full text |Cite
|
Sign up to set email alerts
|

Protein and Energy Intake Assessment and Their Association With In-Hospital Mortality in Critically Ill COVID-19 Patients: A Prospective Cohort Study

Abstract: Background and Aim: It is partially known that nutritional intake could alleviate proteolysis and course of disease severity in patients with COVID-19; however, not enough data are available in this regard. The present study aimed to assess protein and energy intake and their association with in-hospital mortality in critically ill COVID-19 patients.Methods: A total of 126 patients with COVID-19, who were critically ill, ≥5 days and a subset of 111 patients in ICU ≥10 days completed the present prospective obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
0
11
0
3
Order By: Relevance
“…The literature on the prevalence of malnutrition according to the GLIM criteria in the ICU is still scarce, ranging from 18% to 68%. [16][17][18][19][20]27,28 A prevalence of <20% was reported in three studies with some particularities: a study involving overweight patients with COVID-19 (mean BMI, 27.8) that did not assess reduced muscle mass (18%), 27 a…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the prevalence of malnutrition according to the GLIM criteria in the ICU is still scarce, ranging from 18% to 68%. [16][17][18][19][20]27,28 A prevalence of <20% was reported in three studies with some particularities: a study involving overweight patients with COVID-19 (mean BMI, 27.8) that did not assess reduced muscle mass (18%), 27 a…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, the protein level must be indicated, as this nutrient may be crucial for critically ill patients [ 47 ]. This results from the fact that the protein intake in the early acute phase of COVID-19 infection was associated with better survival and lower risk of in-hospital mortality [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in undernourished children have shown that protein and energy malnutrition contribute to an increased risk of severe infection by reducing CD8+ T cell responses [ 52 , 53 , 54 ]. Higher intakes of protein and energy intake have been associated with better survival in critically ill COVID-19 patients by one study [ 55 ]. We found no relation between protein and energy intake and symptom severity in our study.…”
Section: Discussionmentioning
confidence: 99%